Total transfemoral approach for Gore Excluder thoracoabdominal branch endoprosthesis (TAMBE), external tour de graft technique - Saurabh Gupta, MD; Joshua Plant, MD; Javaneh Jabbari, MD; Arian Savadkohi; Shahab Toursavadkohi, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Total transfemoral endovascular repair of thoracoabdominal aneurysms is feasible with physician-modified endografts. We present our technique for exclusively delivering the Gore Excluder thoracoabdominal branch endoprosthesis (W. L. Gore & Associates) via transfemoral access. A 16 Fr steerable sheath is positioned outside the partially deployed thoracoabdominal branch endoprosthesis device, and the preloaded wires are individually snared, allowing for a stable 8 Fr coaxial system to cannulate and deliver stents to target vessels. This technique avoids upper extremity access and maintains all wires within the descending thoracic aorta, allowing implantation in patients with challenging aortic arch configurations and potentially mitigating stroke risk.